O możliwościach ekumenicznej współpracy katolików i luteranów nad kształtowaniem decyzji ustawodawcy polskiego w dziedzinie małżeństwa i rodziny - Piotr Kroczek (Polonia Sacra)
In present times, there are many threats to the marriage and the family. Among other things the risks come from provisions of law that is drafted without regard for Christian roots of the European civilization. In the face of the situation, the Christian Communities are called to start an ecumenical dialog and to undertake a practical action to promote their common Christian paradigm of the marriage and the family that would be a pattern for a state legislator. It is possible in Poland, because the teaching of the Catholic Church and the Evangelical Church of the Augsburg Confession in Poland about the marriage and the family have in terms of content much in common. Additionally, there are many legal possibilities, like, e.g., legislative initiative, to undertake such a promotion of Christian paradigm.